Konsep Keabadian dan Waktu dalam Perspektif Pemikiran Islam - Oktarika, Dina (UIN Sumatera Utara, 2023)
Intellectual pluralism which refers to a variety of views and approaches in understanding Islamic teachings, which allows different interpretations of certain aspects of Islamic beliefs and philosophy which focuses on the concepts of